Pengembangan Bahan Ajar Model Pjbl Berbasis Ideal Stage Untuk Meningkatkan Kemampuan Problem Solving Mahasiswa - amrullah, amrullah; Karolina, Asri; Fernandes, Ebi; Mediansyah, Fajri; Amrullah., amrullah (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2025)
Project-Based Learning significantly enhances students' creative thinking skills through project-based assignments. Teaching materials emphasizing this model empower students to independently develop ideas and concepts. This study aims to develop a valid, practical, and effective Project-Based Learning model based on the Ideal Stage framework to improve problem-solving skills among graduate students in the Islamic Education Study Program at IAIN Curup. The research employed the Research and Development (R&D) method, adapting Borg & Gall's 10-cycle procedural model. Findings show that 94.85% of lecturers and 78.39% of students expressed the need for Ideal Stage-based Project-Based Learning materials in the graduate environment of IAIN Curup. Expert evaluations rated the Islamic Education Philosophy teaching materials with an average score of 88.475, categorized as highly feasible within the 80–100% range. Pre-test results for students' collaboration skills showed a t-value lower than the t-table (0.994 < 2.000), while post-test results for problem-solving skills indicated a t-value higher than the t-table (19.614 > 2.000). These findings demonstrate that the syntax and teaching materials for Islamic Education Philosophy based on the Ideal Stage framework significantly and effectively improve students' problem-solving skills.